SYSTEM IDENTIFICATION APPLIED ON VARIOUS FORMS OF CONTROL TANK SYSTEM - MICHAEL, ALWIN PRAKASH (Universiti Teknologi PETRONAS, 2007)
Control Tanks are widely used and are considered as general equipment in the industry today. Therefore, it is required to have a good control system or control analysis specifically for the system. For any control analysis, it is desirable to be able to obtain a model of the tank system to allow complete off-line analysis with minimum interference to the process. This paper concerns the system identification of various form of control tank system used in the industry today. It simplifies the approach to identification and presents the use of analysis in a more readable, understandable and general manner. Through mathematical modelling, MATLAB simulation and technical computing the whole system can be characterized based on the relevant parameters for a variety of tank formations. This method presents the user to identify and know the system characteristic of the control tank system through simulation study and hence, help to design the best possible operating method to be used in real industry application. Through this simulation study, each type of system can be characterized individually and independently based on the flow rate and the height of the tank. Initially through mathematical derivation, the modelling is then performed and simulated using the Simulink application in MATLAB. An important stage in system identification process is the selection of the type and characteristics of each type of the tank system and this is the subject of this paper.